Development of industrial competitive analysis tools - V. N. Parakhina; O. V. Berezhnaya; D. B. Gegaeva; D. A. Duginets; I. I. Leush (Вестник Северо-Кавказского федерального университета, 2022)
The purpose of the work is the improvement and industry specification of competitive analysis methods with the identification of the complexities and weaknesses of traditional tools and their modification to level these shortcomings. The work uses modern methods and tools of competitive analysis, based, among other things, on statistical evaluation methods and a comparative approach. The information base was made up of EMISS data and organizations of specific industries and markets, including open data, website information and financial reporting. The results of the study represent an assessment of competitiveness and competition in individual markets, a demonstration, systematization and testing of industry-specific features of applying traditional methods for analyzing the competitive environment. Further research in this area, according to the authors, should continue the processes of systematization of special indicators, methods and information databases for evaluating competitors in various industry markets, their development and the formation of evaluation templates for larger studies.